Java with object-oriented programming - Wang, Paul S.
Paul Wang's JAVA WITH OBJECT-ORIENTED PROGRAMMING eases students into an understanding of the object-oriented paradigm from the very first page, just as he does in JAVA WITH OBJECT-ORIENTED PROGRAMMING WITH WORLDWIDE WEB APPLICATIONS, on which this new book is modeled. After the early chapters that present classes and Java features and constructs, Wang introduces new object-oriented concepts throughout the book, while clearly showing how Java addresses these issues. He also goes the extra step of including case studies to illustrate how Java and object-oriented programming are applied. Early in the book, Wang introduces students to a case study involving a pocket calculator. This case study is revisited throughout the book as students learn new aspects of object-oriented programming and the Java language. The book then concludes with a chapter on some of the processes associated with object-oriented design. As a result, students are able to fully grasp the concepts they learn.